PENGEMBANGAN SISTEM INFORMASI PERSEDIAN BARANG BERBASIS DESKTOP DENGAN METODE RAD PADA CV MENEMBUS BATAS - Farid Wajdillah; Suherman Suherman; Muhammad Makmun Effendi (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
In the era of globalization and increasingly fierce business competition, the company's operational efficiency is an important key in achieving greater profits. Good and effective inventory management is one of the factors that affect operational efficiency. CV Menembus Batas, a plastic waste recycling company, faces efficiency problems due to the use of manual systems in processing inventory data. This leads to slow data processing processes, inventory miscalculations, and other problems. To overcome this problem, CV Menembus Batas needs to implement the development of a desktop-based inventory information system with the Rapid Application Development (RAD) method. With an integrated information system, companies can speed up the data processing process, improve inventory control, facilitate report generation, and improve the right decision making. The implementation of this inventory information system can improve CV Menembus Batas operational efficiency and provide accurate and fast information.